2001
DOI: 10.1002/ab.1019
|View full text |Cite
|
Sign up to set email alerts
|

Vengeance: Effects of gender, age, and religious background

Abstract: Vengeance can be commonly defined as the infliction of harm in return for perceived injury or insult or as simply getting back at another person. Three hundred fifty-three participants responded to eight hypothetical scenarios that may elicit vengeful behavior in which the offending party was either a romantic partner, a friend, a coworker, or a stranger. Participants also completed a vengeance scale and a measure of biblical literalism. Participants were most vengeful toward coworkers and least vengeful towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 14 publications
7
34
0
4
Order By: Relevance
“…The negative correlation of age with feelings of injustice and disappointment and intent of prevention echoes the results of Cota-McKinley [2001], who reported that the total score on the vengeance scenarios decreased with age. Cota-McKinley offered the tentative explanations that college education and/or 'the wisdom of age' might decrease vengefulness.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The negative correlation of age with feelings of injustice and disappointment and intent of prevention echoes the results of Cota-McKinley [2001], who reported that the total score on the vengeance scenarios decreased with age. Cota-McKinley offered the tentative explanations that college education and/or 'the wisdom of age' might decrease vengefulness.…”
Section: Discussionsupporting
confidence: 72%
“…It was further expected that the closeness of the relationship would impact disappointment and aggression. Following the argument of Cota-McKinley et al [2001], that people are more personally involved in a work relationship than a relationship with a stranger, it was expected that an injustice committed by a coworker would result in more disappointment.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Although these studies as a group suggest that this type of analysis of forgiveness is appropriate regardless of the relationship between the transgressor and the offended party, other studies have found forgiveness and its effectiveness in reducing aggression may be, in part, dependent on the relationship between the individuals involved. For example, Cota-McKinley et al [2001] found significant differences in the predicted vengeful responses to transgressions committed by coworkers and romantic partners, in that vengeance scores were significantly higher after participants read a scenario about a transgressing coworker than when they read about a transgressing romantic partner. Although this study did not address forgiveness directly, it suggests that more forgiveness would be required of coworkers than of romantic partners following a transgression.…”
Section: Introductionmentioning
confidence: 98%
“…Although this study did not address forgiveness directly, it suggests that more forgiveness would be required of coworkers than of romantic partners following a transgression. Cota-McKinley et al [2001] suggest that vengeance, or lack of forgiveness, is driven by the closeness of the relationship, in that individuals are usually less involved with their coworkers than with their romantic partners, and hence are less invested in keeping the relationship with coworkers free from conflict. Similar results have been reported with forgiveness of friends vs strangers, whereby friends are more easily forgiven than strangers [Phillips and Brown, 2002], and between coworkers who are liked and those who are not [Bradfield and Aquino, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Social safeness may well be one of the variables which mediate the relationship between forgiveness and life satisfaction for several reasons: First of all, social safeness is positively correlated with self-esteem and negatively with selfcriticism (Kelly et al, 2012) and therefore decreases vengeful thinking and increases forgiveness because vengeful cognitions are related to restoring self-worth (Cota-Mckinley et al, 2001) and these cognitions might be motivated by the goal of saving face (Mccullough et al, 2001). Second, individuals with feelings of social safeness were less likely to be fearful and insecure in their attachment style which may be related to under-activation of the soothing-affiliation system (Gilbert, 2005;Kelly et al, 2012;Liotti, 2000).…”
Section: Social Safeness As a Mediatormentioning
confidence: 99%